2019
DOI: 10.2494/photopolymer.32.449
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Properties of Novel Fluorescent Polyimide Based on Excited State Intramolecular Proton Transfer at The End Groups

Abstract: Excited state intramolecular proton transfer (ESIPT) is one of the distinctive photophysical processes of fluorescent compounds and polymers, which induces enhanced fluorescence with a very large Stokes shift. In this work, 6FDA/DCHM/3HPA polyimides (PIs) having bulky-CF 3 groups were synthesized, in which 3HPA is an end-group which exhibits ESIPT with enhanced green emission when irradiated by UV light at 365 nm. Introduction of bulky side chains can improve fluorescent properties via suppression of aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, since it has been reported that PI films with acid dianhydrides, such as PMDA and BPDA, emit fluorescence in the visible region, the improvement of the fluorescence property of PI is desired [16][17][18][19]. To suppress the CT and LE(n−π*) transitions and enhance the LE(π−π*) transitions between the S 0 and S 1 states, we have developed a series of highly fluorescent PIs with high Φ values by combining dianhydrides with high electron-accepting ability, whose HOMO-LUMO transitions are LE(π−π*), and alicyclic diamines with low electrondonating ability [15,[20][21][22][23][24][25][26][27][28][29]. With other methods, highly fluorescent fully aromatic PIs have been developed by introducing aggregation-induced emission (AIE)-active bulky moieties, such as modified triarylamine [30,31] or tetraphenylethylene structures [32], in their main or side chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since it has been reported that PI films with acid dianhydrides, such as PMDA and BPDA, emit fluorescence in the visible region, the improvement of the fluorescence property of PI is desired [16][17][18][19]. To suppress the CT and LE(n−π*) transitions and enhance the LE(π−π*) transitions between the S 0 and S 1 states, we have developed a series of highly fluorescent PIs with high Φ values by combining dianhydrides with high electron-accepting ability, whose HOMO-LUMO transitions are LE(π−π*), and alicyclic diamines with low electrondonating ability [15,[20][21][22][23][24][25][26][27][28][29]. With other methods, highly fluorescent fully aromatic PIs have been developed by introducing aggregation-induced emission (AIE)-active bulky moieties, such as modified triarylamine [30,31] or tetraphenylethylene structures [32], in their main or side chains.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, white emission, which requires long-wavelength fluorescence with a very large ν, is challenging to achieve. To overcome this problem, the uses of excited-state intramolecular proton transfer (ESIPT) and intersystem crossing (ISC) followed by phosphorescence emission are advantageous [21,28,33]. In addition, molecules having a donor-acceptor structure exhibit large Stokes-shifted fluorescence owing to the effective spatial separation of HOMO and LUMO [34].…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit large Stokes-shifted orange and green FL through an excited state intramolecular proton transfer (ESIPT). 13–19…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit large Stokes-shifted orange and green FL through an excited state intramolecular proton transfer (ESIPT). [13][14][15][16][17][18][19] Recently, metal-free room-temperature phosphorescence (RTP) has attracted significant attention owing to the very large Stokes shifts and ultra-long luminescence lifetime. 20,21 In general, phosphorescence is rarely observed at RT in air because it is easily deactivated by local molecular motions and quenching by atmospheric oxygen during the long lifetime of the excited triplet (T 1 ) state.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PIs have been applied in numerous fields, including automotive, microelectronic, photonic, electronic, and aerospace industries. Owing to their characteristic photoluminescence (PL) properties and excellent performance, PI films have been extensively studied as novel thermally stable photoluminescent materials [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%